2011
DOI: 10.1128/aem.01496-10
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation in Enterococcus faecalis of Dose-Dependent Resistance and Cross-Resistance to Pore-Forming Antimicrobial Peptides by Use of a Polydiacetylene-Based Colorimetric Assay

Abstract: A better understanding of the antimicrobial peptide (AMP) resistance mechanisms of bacteria will facilitate the design of effective and potent AMPs. Therefore, to understand resistance mechanisms and for in vitro assessment, variants of Enterococcus faecalis that are resistant to different doses of the fungal AMP alamethicin (Alm r ) were selected and characterized. The resistance developed was dose dependent, as both doses of alamethicin and degrees of resistance were colinear. The formation of bacterial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The emergence and spread of resistance against known bacteriocins in food spoilage and pathogenic bacteria would threaten the safety of using bacteriocins as food preservatives [ 19 ]. The target bacteria adopt various strategies to overcome the effect of antimicrobial agents by either altering the cell envelope composition which no more remains a suitable target for AMPs or forming bacterial cell clumps by aggregation of large number of bacteria [ 15 , 22 , 23 ]. S. aureus is highly resistant to antimicrobial factors of the innate immune system such as cationic antimicrobial peptides (CAMPs) [ 14 ], which are produced by epithelial cells and neutrophils [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence and spread of resistance against known bacteriocins in food spoilage and pathogenic bacteria would threaten the safety of using bacteriocins as food preservatives [ 19 ]. The target bacteria adopt various strategies to overcome the effect of antimicrobial agents by either altering the cell envelope composition which no more remains a suitable target for AMPs or forming bacterial cell clumps by aggregation of large number of bacteria [ 15 , 22 , 23 ]. S. aureus is highly resistant to antimicrobial factors of the innate immune system such as cationic antimicrobial peptides (CAMPs) [ 14 ], which are produced by epithelial cells and neutrophils [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pedA gene encoding pediocin was detected using PCR and sequenced [ 17 ]. Pediocin produced was purified by three-step purification procedure, which included ammonium sulfate precipitation, cation-exchange chromatography, and reverse-phase high-performance liquid chromatography [ 15 ]. The purity and antimicrobial activity of the pediocin fraction were checked using SDS-PAGE [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After culturing for 24 h, we measured absorbance at 600 nm (A 600 ). We used this value to calculate the percentage of inhibition (%I) as follows: %I ϭ 1 Ϫ (Ac/Ao) ϫ 100, where Ac is the A 600 of the culture at a given concentration of drugs, and Ao is the A 600 of the positive control (19). We then determined the IC 50 as the concentration of drugs resulting in 50% inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…So far, it is suggested that peptides show cross resistance when they share common mechanisms of action [191], but this assumption should be further evaluated. In addition, in some cases the resistance to the AMPs was abolished after removing the AMP [129,190,192].…”
Section: Accepted Manuscriptmentioning
confidence: 99%